Carausius and His Brothers: The Construction and Deconstruction of an Imperial Image in the Late Third Century AD. (2019) - Davenport, Caillan
Abstract: This article examines the public image of the emperor Carausius, a Roman army officer who claimed authority over Britain and parts of Gaul between 286 and 293, in opposition to Diocletian and his Tetrarchic colleagues. Carausius' coinage celebrated his fleet, his naval prowess, and his divine support from Neptune and Oceanus. These designs were created as part of a strategy to refashion Carausius' humble background as a sailor into a statement of imperial suitability. However, Carausius' claims were undermined by the orators who delivered speeches in praise of his Tetrarchic rivals, Maximian and Constantius, in the years 289, 291, and 297. Their panegyrics subverted Carausius' naval experience and claim to control the Ocean, instead portraying him as a pirate, brigand, and threat to the people of Gaul. After the reconquest of Britain, the medallions and monuments of the Tetrarchic regime commemorated their own naval success and control over the Ocean, suppressing the claims of Carausius. The propaganda campaign against Carausius was driven by the fact that he was an emperor of undistinguished origin, who had risen up through the ranks of the army, just like the Tetrarchs themselves. The emperors wished to distance themselves from their former colleague in order to discourage further rebellion from within the officer corps.